The Literature of “Socialist Humanism”: Compassion as a Variation of Ideological Manipulation - Tūtlytė, Rita (Literatūra, 2018)
[article in Lithuanian; only abstract in English] In this article, we examine the “socialist humanism” that unfolds in Mykolas Sluckis’s novel Laiptai į dangų (Stairway to the Skies, 1963); we examine the contents, rhetorical means for building the text and the forms of ideological expression of said “socialist humanism.” In deconstructing the text, we put emphasis on the strategies of suggestion. One of such strategies is the following one: an individual wronged by destiny, one in need of care and compassion, is thrown into a whirlwind of political events. In such a way, the conflict of ideologies is transferred into the domestic environment and the psychological realm. A “naked” political argumentation is refused, and emotions are instead utilized for suggestion. The figure of the cripple, which appeared in the works of the “socialist humanism” program, provides the said cripple figure with a dimension of humanity and links it with tradition; on the other hand, it is also manipulated. An idea is being instilled that the only society that can be created on the principles of mutual aid and compassion is the socialist society. We study in the article whether the rhetorical operations of the novel, and especially the novel’s ending, affirm these ideological schemes or demonstrate their ambiguity. Several methods of suggestion employed by the author are observable: an emotional love story is being narrated with the help of inner monologues, the presented characteristics of the story’s characters are tendentious, the ambivalence of aposiopeses and hints is maintained, deliberate comments are inserted, passions relating to pity are being manipulated, and the relationships between parents and children have an undertone resembling Pavlik Morozov, the parents’ traitor. The unfurled paradigm of compassion in Sluckis’s book aids in understanding the reception of “socialist humanism” in the Soviet-era society of Lithuania – to understand why manipulation based on the means of kindness and compassion was being rejected in the underground movements of the Soviet period. What is also observable is that in the 1980s, literature works of the silent modernism gave a new sense to the portrayal of the cripple: the cripple of the last generation, manipulated and devoid of any autonomous value, is opposed by the cripple as a free individual who possesses an independent worldview